Pop-up restoration in colonial contexts: applying an indigenous food systems lens to ecological restoration - Grenz, Jennifer; Armstrong, Chelsey Geralda (Frontiers in Sustainable Food Systems, 2023)
As environmental injustices and their disproportionate harms to Indigenous communities are increasingly acknowledged, restoration strategies are being deployed widely by environmental NGOs, resource extraction industries, and government agencies. The inclusion of Indigenous communities and their knowledges in restoration efforts are often considered progress in the pursuit of ecological reconciliation. However, in some cases we have observed a lack of meaningful progress as settler colonial prescriptions for land-healing can eschew efforts to decolonize ecological restoration — what we have labeled “pop-up restoration.” We consider two restoration efforts underway in St’at’imc and Quw’utsun territories (Canada) and contrast them with what we are learning alongside the communities’ own values and efforts to reclaim and revitalize food systems throughout forest, wetland, and grassland systems. Utilizing culturally appropriate pathways, we then evaluate how applying an Indigenous Food Systems lens to ecological restoration may provide a framework to remedy pop-up restoration, confronting settler colonial aspirations to transform Indigenous homelands while asserting justice in ecological restoration contexts.